Allegedly : a novel - Jackson, Tiffany D. (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2017)
When Mary, a teenager living in a group home, becomes pregnant, authorities take another look at the crime for which Mary was convicted when she was nine years old.